Adoption of green manufacturing in Indian manufacturing industry: a fuzzy analytical hierarchy process approach for inhibitors. (2017) - Mittal, Varinder Kumar
Green manufacturing (GM) has been considered a boon to counter the environmental impact of manufacturing. The challenges of implementing GM in developing countries need to be addressed carefully because of their scarce expertise and resources. The adoption of GM initiatives is not realised in majority of MSMEs due to some issues which are named as 'inhibiting factors'. It is extremely difficult to implement GM without mitigating the issues hindering the adoption process. So, in this paper, an attempt has been made to apply fuzzy AHP to rank the factors inhibiting the adoption of GM in India. The research concluded that uncertain benefits of green technology, high short term cost, and lack of awareness/information among the managers and decision makers are the three most important inhibitors. It is expected that this research will provide help to the policy makers to frame policies facilitating the faster adoption of GM.